Research advances of endothelial-mesenchymal transition during peritoneal dialysis-related peritoneal fibrosis - Liao Meng; Chen Si-jie; Tang Ri-ning; Zhang Xiao-liang (Linchuang shenzangbing zazhi)
Peritoneal dialysis is one of renal replacement therapies for patients with end-stage renal disease（ESRD）.Peritoneal dialysis-related peritoneal fibrosis is the most important reason for withdrawing peritoneal dialysis in ESRD patients.Previous studies have hinted that a major mechanism of peritoneal fibrosis is epithelial-mesenchymal transition（EMT）.Recentstudies have found that endothelial-mesenchymal transition（EndMT）may be one of the mechanisms of peritoneal fibrosis.High glucose, inflammation and oxidative stress affect the occurrence and development of EndMT in peritoneal tissues.This review summarized the latest advances of EndMTduring peritoneal dialysis-related peritoneal fibrosis.